Front Cover: BF4− as source for the preparation of BF2 bridged copper(II) dimethylglyoxime complexes (Z. Anorg. Allg. Chem. 16/2022). Issue 16 (18th August 2022) - Petrikat, Raphael I.; Becker, Sabine
Abstract : The cover picture shows a closer look at the decomposition of the tetrafluoroborate anion (BF4 ‐ ) during the reaction of Cu(BF4 )2 ⋅6H2 O and dimethylglyoxime (H2 dmg) to formally "BF2 + " and 2F ‐ . Whereas the high affinity of fluoride anions towards silicon lead to the formation of SiF6 2‐, BF2 is inserted into the ligand framework to yield diverse O, O‐bidentate difluoroboron copper(II) complexes. These resulting complexes have been isolated and structurally characterized. Their molecular structures frame the magnifying glass that highlights the decomposition of BF4 ‐ . (DOI: 10.1002/zaac.202200150 ).